Sulforaphane inhibits the growth of prostate cancer by regulating the microRNA-3919/DJ-1 axis - Zhang, Fangxi; Wan, Xiaofeng; Zhan, Jianmin; Shen, Ming; Li, Runsheng (Frontiers in Oncology, 2024)
Background Prostate cancer (PCa) is the second most common solid cancer among men worldwide and the fifth leading cause of cancer-related deaths in men. Sulforaphane (SFN), an isothiocyanate compound, has been shown to exert inhibitory effects on a variety of cancers. However, the biological function of SFN in PCa has not been fully elucidated. The objective of this study was conducted to further investigate the possible underlying mechanism of SFN in PCa using in vitro cell culture and in vivo tumor model experiments. Methods Cell viability, migration, invasion, and apoptosis were analyzed by Cell Counting Kit-8 (CCK-8), wound healing assay, transwell assay, or flow cytometry. Expression of microRNA (miR)-3919 was detected by quantitative real-time polymerase chain reaction (qRT-PCR) or in situ hybridization assay. Xenograft assay was conducted to validated the antitumor effect of miR-3919. The targeting relationship between miR-3919 and DJ-1 was verified by dual-luciferase reporter assay. The level of DJ-1was measured by qRT-PCR or western blotting (WB). Results In the present study, SFN downregulated mRNA and protein expression of DJ-1, an oncogenic gene. Small RNA sequencing analysis and dual-luciferase reporter assay confirmed that microRNA (miR)-3919 directly targeted DJ-1 to inhibition its expression. Furthermore, miR-3919 overexpression impeded viability, migration, and invasion and promoted apoptosis of PCa cells. Tumor growth in nude mice was also inhibited by miR-3919 overexpression, and miR-3919 expression in PCa tissues was lower than that in peritumoral tissues in an in situ hybridization assay. Transfection with miR-3919 inhibitors partially reversed the effects of SFN on cell viability, migration, invasion, and apoptosis. Conclusion Overall, the miR-3919/DJ-1 axis may be involved in the effects of SFN on the malignant biological behavior of PCa cells, which might be a new therapeutic target in PCa.